Phenotypic and Functional Analysis of Human NK Cell Subpopulations According to the Expression of FcεRIγ and NKG2C - Kim, Kyung Hwan; Yu, Hee Tae; Hwang, Ilwoong; Park, Sungha; Park, Su-Hyung; Kim, Sungjin; Shin, Eui-Cheol (Frontiers in Immunology, 2019)
Human memory-like NK cells are commonly defined by either a lack of FcεRIγ or gain of NKG2C expression. Here, we investigated the heterogeneity of human CD56dim NK cell subpopulations according to the expression of FcεRIγ and NKG2C in a large cohort (n=127). Although the frequency of FcεRIγ– and NKG2C+ NK cells positively correlated, the FcεRIγ– and NKG2C+ NK cell populations did not exactly overlap. The FcεRIγ+NKG2C+, FcεRIγ–NKG2C+, and FcεRIγ–NKG2C–¬ NK cell populations were only evident after HCMV infection, but each had distinct characteristics. Among the subpopulations, FcεRIγ–NKG2C+ NK cells exhibited the most restricted killer immunoglobulin-like receptor repertoire, suggesting clonal expansion. Moreover, FcεRIγ–NKG2C+ NK cells exhibited the lowest Ki-67 and highest Bcl-2 expression, indicating the long-lived quiescent memory-like property. Functionally, FcεRIγ–NKG2C+ NK cells had weak natural effector function against K562 but strong effector functions by CD16 engagement, whereas FcεRIγ+NKG2C+ NK cells had strong effector functions in both settings. Anatomically, the FcεRIγ+NKG2C+, FcεRIγ–NKG2C+, and FcεRIγ–NKG2C–¬ NK cell populations were present in multiple human peripheral organs. In conclusion, we demonstrate the heterogeneity of memory-like NK cells stratified by FcεRIγ¬ and NKG2C and suggest both markers be utilized to better define these cells.